Rising trend in cesarean sections: a retrospective study at tertiary care hospital in Jammu - Zargar, Shazia; Gandotra, Nikita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The uncontrolled wave of cesarean rates has increased globally which has resulted in a significant amount of maternal mortality and morbidity. The present study aims to evaluate the trend in cesarean section rates in Jammu, India. Methods: The present retrospective study was carried out at the department of Obstetrics and Gynecology, SMGS Hospital, Jammu, India. We collected data based on total number of deliveries and cesarean sections performed at the hospital during (March2015-Feb2020) along with indications for CS. Results: The percentage of cesarean sections has increased drastically from 39.4% during (2015-16) to 49.9% in (2019-20). The study shows that the most common indication for CS is post CS followed by NPOL, Fetal distress, breech, APH, CPD, PIH and others. Conclusions: There is a growing concern among public and health care providers regarding the escalating and uncontrolled trend of cesarean sections which needs to be curtailed within optimal limits recommended by WHO.